Multichannel signal enhancement algorithms for assisted listening devices: Exploiting spatial diversity using multiple microphones - Doclo, S.; Kellermann, W.; Makino, S.; Nordholm, Sven (Institute of Electrical and Electronics Engineers Inc., 2015)
In everyday environments, we are frequently immersed by unwanted acoustic noise and interference while we want to listen to acoustic signals, most often speech. Technology for assisted listening is then desired to increase the efficiency of speech communication, reduce listener fatigue, or just allow for enjoying undisturbed sounds (e.g., music). For people with normal hearing, assisted listening devices (ALDs) mainly aim to achieve hearing protection or increase listening comfort; however, for hearing-impaired individuals, as the most prominent user group so far, further progress of assisted listening technology is crucial for better inclusion into our world of pervasive acoustic communication.